Application of Additive Manufacturing Technology for Chair Parts Connections - Nicolau, Antoniu; Pop, Mihai Alin; Georgescu, Sergiu Valeriu; Coșereanu, Camelia (MDPI AG, 2023)
Additive manufacturing (AM) is a potential technology to be applied for replacing wood joints in the furniture industry. Overall, 3D-printed connectors have a lot of advantages in chair construction: the possibility of improving the design by using colored materials and new concepts with no limits of shape and size, avoiding the use of synthetic materials such as adhesives and finishing materials. The present research shows the results of the research conducted on 3D-printed connectors for a chair leg-stretchers joint. Larch (Larix decidua Mill.) wood was used for chair components and selective laser sintering (SLS) technology was employed for the 3D-printing connector designed to assemble the chair elements. Diagonal tensile and compression tests were performed on the L-type joints with 3D-printed connectors and the bending moments were determined and compared to the results obtained after testing the leg-stretchers mortise–tenon joints made of larch wood, taken as a reference. Micrograph investigation was finally performed on the broken areas of the 3D-printed connectors as a result of mechanical testing failures. The results show that the SLS printing technology applied to build the connector does not ensure enough strength to the assembly, and changes in printing parameters are needed for further research, in terms of laser power and scan speed.
Keywords: additive manufacturing; 3D printing; chair parts; connector